A Novel Risk-Score Model With Eight MiRNA Signatures for Overall Survival of Patients With Lung Adenocarcinoma - Wu, Jun; Lou, Yuqing; Ma, Yi-Min; Xu, Jun; Shi, Tieliu (Frontiers in Genetics, 2021)
Lung adenocarcinoma (LUAD) is the most common subtype of lung cancer with heterogeneous outcomes and diverse therapeutic responses. To classify patients into different groups and facilitate the suitable therapeutic strategy, we first selected 6 miRNA signatures in the TCGA-LUAD cohort based on multi-strategy combination, including differential expression analysis, regulatory relationship, univariate survival analysis, importance clustering and multi-variate combinations analysis. Using the 8 miRNA signatures, we further built a novel risk-scores based on the pre-defined cutoff and beta coefficients and divided the patients into high-risk and low-risk groups with significantly different overall survival time (p-value < 2e-16). The risk-score model was confirmed with an independent dataset (p-value = 4.71e-4). We also observed that the risk scores of patients of early-stage were significantly lower than that of late-stage patients. Moreover, our model can also provide new insights into the current clinical staging system and can be regarded as an alternative system for patient stratification. This model unified the variable value as the beta coefficient facilitating the integration of biomarkers obtained from different omics data.